2020
DOI: 10.1055/s-0040-1715449
|View full text |Cite
|
Sign up to set email alerts
|

The Spectrum of Disease Severity in Cirrhosis and Its Implications for Hemostasis

Abstract: Bleeding and thrombosis are both common complications that patients with advanced liver disease experience. While hemostatic pathways remain largely intact with cirrhosis, this balance can quickly shift in the direction of bleeding or clotting in an unpredictable manner. A growing body of literature is attempting to shed light on difficult scenarios that clinicians often face, ranging from predicting and mitigating bleeding risk in those who need invasive procedures to determining the best strategies to manage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 64 publications
0
10
0
1
Order By: Relevance
“…Patients with cirrhosis can present with a wide spectrum of diseases, from well‐compensated cirrhosis to chronic decompensation to acute decompensation with multiorgan failure. ( 40 ) Advanced liver disease is associated with thrombocytopenia attributable to portal hypertension and a prolonged INR as a result of an impaired synthesis of coagulation factors. Although these coagulation indices are historically used to assess bleeding risk, they are misleading in patients with cirrhosis.…”
Section: Liver Disease Factorsmentioning
confidence: 99%
“…Patients with cirrhosis can present with a wide spectrum of diseases, from well‐compensated cirrhosis to chronic decompensation to acute decompensation with multiorgan failure. ( 40 ) Advanced liver disease is associated with thrombocytopenia attributable to portal hypertension and a prolonged INR as a result of an impaired synthesis of coagulation factors. Although these coagulation indices are historically used to assess bleeding risk, they are misleading in patients with cirrhosis.…”
Section: Liver Disease Factorsmentioning
confidence: 99%
“…Only recently have studies begun to address the haemostatic status in critically ill patients with cirrhosis (i.e., those with acutely decompensated cirrhosis [AD] and acuteon-chronic liver failure [ACLF]). 11 Fisher and coworkers provided initial evidence that the haemostatic balance in patients with AD and ACLF remains in equilibrium, despite progressive deterioration in routine haemostatic tests (platelets, INR) and levels of individual haemostatic proteins. 24 The same group subsequently confirmed and extended these findings.…”
Section: Pathogenesis Of Bleedingmentioning
confidence: 99%
“…We will specifically focus on recent breakthroughs and do not intend to give a complete overview of the field which is covered elsewhere. [8][9][10][11][12][13]…”
Section: Introductionmentioning
confidence: 99%
“…[ 28 31 ] These findings might be partly explained by a significant decrease on thrombomodulin-mediated inhibition of thrombin [ 32 ]. Nevertheless, the predisposition for bleeding in both acute and chronic liver diseases remains controversial, [ 33 ] and some experts suggested that the liver inflammation might be a potential predictor for bleeding [ 34 ]. In this context, the association between liver enzymes at VTE diagnosis and a higher risk for bleeding or to die might help to establish the basis for an association between the thrombosis–bleeding balance and the liver status in patients with undetected hepatic disease.…”
Section: Discussionmentioning
confidence: 99%